Search for decays of the Higgs boson into a pair of pseudoscalar particles decaying into bb[bar]τ + τ − collisions at √s=13 TeV with the ATLAS detector - Aad, Georges; Ackermann, Anke; Baltes, Lisa Marie; Bartels, Falk; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; Sanfilippo, Lorenzo; et al. (Physical review, 2024)
This paper presents a search for exotic decays of the Higgs boson into a pair of new pseudoscalar particles, , where one pseudoscalar decays into a -quark pair and the other decays into a -lepton pair, in the mass range . The analysis uses collision data at collected with the ATLAS detector at the LHC, corresponding to an integrated luminosity of . No significant excess above the Standard Model (SM) prediction is observed. Assuming the SM Higgs boson production cross section, the search sets upper limits at 95% confidence level on the branching ratio of Higgs bosons decaying into , bb̄τ+τ-, β(H → aa → bb̄τ+τ-), between 2.2% and 3.9% depending on the pseudoscalar mass.